An Analytic-Evaluative Study of Class Room Teaching of Effective Education Teacher (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This qualitative research study identified criteria for teacher quality preferences as perceived by current and past stu¬dents. A two-question, open-ended survey asking what qualities learners liked most and least in a teacher/presenter was given to two groups: students (Group A) from medicine, dentistry, and related residency programs; and dentists and physicians (Group B) who had graduated at least three years previously and who attended a minimum of two days of continuing education courses in lecture format each year. A total of 300 subjects provided 2,295 written responses. Descriptive words within the responses were coded and grouped according to similar relationships, resulting in the emergence of twenty-one defined categories that were fur¬ther refined into three core categories: personality, process, and performance. Results showed that the two groups appear to have different preferences in teacher/presenter characteristics. For Group A (students), the categories of content design, content orga¬nization, and content development were at the forefront of their preferences. Group B (professionals) overwhelmingly favored elements of speaker self-confidence and expertise. Both groups highly valued expertise and speaking style. These findings can be used to develop curriculum, enhance faculty members’ teaching skills, and plan continuing education programs.